Diversità funzionale in cloni di ciliegio da legno (Prunus avium L.) di provenienza Appennino toscano - Cutini, Andrea; Giannini, Tessa (Annals of Silvicultural Research, 2026)
Functionality in wild cherry (Prunus avium L.) clones of Tuscany Appenines provenances. Results of a research regarding the functionality of already selected wild cherry (Prunus avium L.) clones are reported. The main target was to select the genotypes with the best ecological efficiency and less sensible to environmental stress, in order to give concrete indications for arboriculture for wood productions. Starting from 2002, measurements were carried out in the experimental plot of Papiano (Stia, AR), where the following clones with provenance from the Tuscan Apennines were compared: Casina Alpe 1 (A), Casina Alpe 2 (D), Puzzòlo (C), Paradisino (E), Piantata Catenaia (F). Dendrometrical data were collected at the beginning and at the end of each season, in order to evaluate the growth and the individual current increment of the clones. To better characterize the canopies of each clone, measurements of photosynthetic active radiation (PAR) and of the leaf area index (LAI) where carried out with ceptometers and PCA LAI 2000. In order to evaluate differences between the clones regarding functionality and response to environmental stress, growth and productivity were related to the most important canopy characteristics. Ecological efficiency was calculated for the different clones using the net assimilation rate (NAR). The results show that the clone E has the most developed canopies and the best results in terms of growth. But at the same time it also presents densely branched round canopies and results more sensible to the effects of summer drought. These elements contribute to advise against the use of this clone in future genetic improvement programs and in high quality wood productions. On the contrary, the clones C and A have both good growth characteristics and a better general architecture and are therefore advised for high quality wood productions especially in the same geographic region.